2022
DOI: 10.3390/nu14132771
|View full text |Cite
|
Sign up to set email alerts
|

Negative Physical Self-Concept Is Associated to Low Cardiorespiratory Fitness, Negative Lifestyle and Poor Mental Health in Chilean Schoolchildren

Abstract: Background: Evidence suggests that physical self-concept (PSC) is linked to well-being in children and adolescents. Objective: The objective was to investigate the association of PSC with mental health (i.e., depression and body image), physical status (i.e., fitness and weight status) and lifestyle (physical activity (PA) patterns and nutritional level) in Chilean schoolchildren. Methods: A total of 617 schoolchildren (n = 271 girls and n = 346 boys) aged 10–14 years participated in this study. Self-concept, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…Throughout life, brain and cognition health among adolescents and young adults can influence academic achievement and overall health [ 1 , 2 ], which necessitates the identification of the predictors and modifiers of brain health at a young age [ 3 ]. Due to advances in the social economy, there has been a growing interest in the influence of lifestyle factors, such as regular physical exercise, in the promotion of a relatively high level of cardiorespiratory fitness (CRF) and health (e.g., brain health) [ 2 , 4 , 5 , 6 ]. CRF is operationalized by maximal oxygen consumption (VO 2 max) and is correlated with the functions of different physiological systems [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Throughout life, brain and cognition health among adolescents and young adults can influence academic achievement and overall health [ 1 , 2 ], which necessitates the identification of the predictors and modifiers of brain health at a young age [ 3 ]. Due to advances in the social economy, there has been a growing interest in the influence of lifestyle factors, such as regular physical exercise, in the promotion of a relatively high level of cardiorespiratory fitness (CRF) and health (e.g., brain health) [ 2 , 4 , 5 , 6 ]. CRF is operationalized by maximal oxygen consumption (VO 2 max) and is correlated with the functions of different physiological systems [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, PA after school and Mediterranean diet adherence positively mediated the link between self-esteem and HRQoL; on the contrary, ST negatively mediated this relation [ 27 ]. In this sense, a previous study showed that high ST and bad food habits were related with poorer mental health; likewise, this study reported that physical fitness dimensions were positively linked with the absence of body image dissatisfaction [ 14 ]. Likewise, a cross-sectional study conducted in children indicated that excessive ST was linked with a high risk of internalizing and externalizing mental health problems; therefore, the authors concluded that it is fundamental to develop healthy lifestyle interventions [ 44 ].…”
Section: Discussionmentioning
confidence: 69%
“…Likewise, it has been indicated that healthy lifestyle was positively related with mental health (i.e., self-esteem) and HRQoL [ 27 ]. Likewise, it has been shown that bad cardiorespiratory fitness was linked with poor physical self-concept in Chilean schoolchildren [ 14 ]. Another study reported that cardiorespiratory fitness was linked with mental health, therefore promoting physical fitness may improve adolescent’s wellbeing [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations